Ujaran Kebencian Terhadap Anies Baswedan di Media Sosial (Kajian Linguistik Forensik) - Putri, Citra Merdeka; Usman, Usman; Haliq, Abdul (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to describe the forms and impacts of language crimes in the form of hate speech against Anies Baswedan on social media. The type of research used is descriptive qualitative research. The data used in this research is text from netizens' tweets and comments on social media taken with screenshots. The data sources in this research come from social. Data collection techniques are carried out by documenting, reading and taking notes. The research instrument in this research is the researcher himself. The data analysis technique in this research is to use descriptive orientation, data reduction, data selection, and conclusions. The results of this research show that there are impacts and forms of hate speech in the form of threats, insults, incitement and defamation against Anies Baswedan on the social media.